Determination of calcium and magnesium in water samples by high-performance liquid chromatography on a graphitic stationary phase with a mobile phase containing o-cresolphthalein complexone - Paull, B; Macka, M; Haddad, PR (Journal of Chromatography A, 1997)
A sensitive and selective liquid chromatographic procedure for the separation and visible detection of alkaline earth metals in complex saline matrices has been developed. A mobile phase containing the selective metallochromic chelating ligand, o-cresolphthalein complexone, was used to dynamically coat a pH tolerant reversed-phase porous graphitic carbon column. A dynamic chelating ion-exchange mechanism facilitated the separation of alkaline earth metals, which were detected using a spectrophotometric detector at 575 nm. Detection limits of 0.05 mg l-1 for magnesium and 0.10 mg l-1 for calcium were obtained in samples containing in excess of 2300 mg l-1 of sodium, without interference. The procedure was applied to the determination of magnesium and calcium in a range of environmental waters, including saturated saline Antarctic lake samples, with the results comparing well to those achieved using capillary electrophoresis, atomic absorption spectroscopy, inductively coupled plasma mass spectrometry and standard complexometric titration methods.